Cerita tentang COVID-19: Efek format pesan pada prasangka terhadap tenaga kesehatan dengan mediasi persepsi ancaman - Boma Baswara; Rizka Halida (Jurnal Psikologi Sosial, 2022)
During the COVID-19 pandemic, there are many cases of prejudice and discrimination against health workers, even though they are the spearhead of the pandemic response. Therefore, this study was conducted to examine the effect of different message types on the prejudice against health workers through the mediating effect of realistic and symbolic threat perceptions of the COVID-19. The message type was manipulated in the aspect of the message format (narrative, statistical) and the depiction of disease threat impact (realistic, symbolic). This research was conducted using a between-subject online experimental survey. The participants were 550 residents of Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) areas. Participants were randomly assigned to one of the conditions, namely statistical message type group, realistic threat narrative, symbolic threat narrative, and control group. After reading the text stimulus, measurements were made on the perception of realistic and symbolic COVID-19 threats, as well as prejudice against health workers. The results showed that the symbolic threat narrative group had lower prejudice compared to other groups (β = -0.226; t(536) = -2.052; p < 0.05). There was no effect of different message formats in the formation of prejudice against health workers. The mediating role of perceived threats on the relationship between message format and prejudice against health workers did not show as well. These results indicated that messages about disease do not always activate the behavioral immune system (BIS) mechanism, but also have the potential to deactivate the BIS mechanism, depending on the disease impact depicted on the message.